Local Ecological Knowledge of the Whitemouth Croaker, Micropologias furneri among the Caiçaras in the Sepetiba Bay, SE Brazil - Morado, Claudio N.; Andrade-Tubino, Magda F. de; Pinto, Benjamin C. T.; Araújo, Francisco G. (Ethnobiology Letters, 2024)
Local Ecological Knowledge of artisanal fishers (Caiçaras) was employed to investigate various biological aspects of the Whitemouth croaker (Micropogonias furnieri) in the Sepetiba Bay, in the state of Rio de Janeiro. This included migration patterns, reproduction, feeding habits, and interactions such as parasitism. Semi-structured interviews were carried out with 40 fishers in two communities using the “snowball” technique. It was found that the fisher’s information coincides with the academic literature for some aspects of the biology and ecology of the species. Furthermore, the fishers provided descriptions of novel patterns, which contributed to a deeper understanding of the species’ natural history. These included observations of reproduction occurring almost throughout the entire year, the influence of east and north winds on the species’ entry into the bay, interactions with marine catfish (Ariidae), and notable records of the isopod Cymothoidae as an important parasite of the Whitemouth croaker. This study contributes new insights to the ecological understanding of this fish species, which holds significant socio-environmental importance. It also documents changes in the livelihoods of artisanal Caiçaras communities resulting from the increasing anthropogenic activities in the region. Finally, it highlights the species’ significance in terms of its sale and consumption within these communities, owing to its relative abundance in the area, despite the environmental impacts.